2021
DOI: 10.3389/fimmu.2021.694355
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Meta-Analysis Reveals Interferon-Induced Genes Associated With SARS Infection in Lungs

Abstract: BackgroundSevere Acute Respiratory Syndrome (SARS) corona virus (CoV) infections are a serious public health threat because of their pandemic-causing potential. This work is the first to analyze mRNA expression data from SARS infections through meta-analysis of gene signatures, possibly identifying therapeutic targets associated with major SARS infections.MethodsThis work defines 37 gene signatures representing SARS-CoV, Middle East Respiratory Syndrome (MERS)-CoV, and SARS-CoV2 infections in human lung cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Given the rapid turnover of IRF1 mRNA and IRF1 proteins, XAF1 has more potential than IRF1 to be a sensitive and reliable diagnostic marker of viral infectious diseases. Our data and other clinical data sets have suggested that elevated XAF1 expression is positively correlated with the SARS-CoV, MERS-CoV, and SARS-CoV-2 infection in the lungs ( 49 , 50 ) as well as the symptoms of the COVID-19 and influenza patients ( 51 ).…”
Section: Discussionsupporting
confidence: 66%
“…Given the rapid turnover of IRF1 mRNA and IRF1 proteins, XAF1 has more potential than IRF1 to be a sensitive and reliable diagnostic marker of viral infectious diseases. Our data and other clinical data sets have suggested that elevated XAF1 expression is positively correlated with the SARS-CoV, MERS-CoV, and SARS-CoV-2 infection in the lungs ( 49 , 50 ) as well as the symptoms of the COVID-19 and influenza patients ( 51 ).…”
Section: Discussionsupporting
confidence: 66%
“…Gao et al (23) found that XAF1 was abnormally strongly expressed in COVID-19 patients and positively correlated with the expression of ARS-CoV-2 invasion-related genes (ACE2, TMPRSS2, CTSB, and CTSL). In contrast, XAF1 was found to be associated with SARS infection by Park and Harris (24). A recent study found that OAS2 belongs to a subset of interferonstimulated genes, and OAS2 can be regarded as a potential candidate for a drug target in COVID-19 therapy (25).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting list of genes along with their T-test scores were used to define 13 gene signatures. This signatures are formed from the gene lists ranked from high to low differential gene expression between tumor versus normal tissue samples (Park & Harris, 2021). The signatures derived from the same dataset used the same control samples.…”
Section: Defining Gene Signaturesmentioning
confidence: 99%
“…Previous work using a GSEA-based meta-analysis approach successfully identified known and novel genes associated with severe acute respiratory syndrome (SARS) infection through differential gene expression comparison between mRNA expression datasets (Park & Harris, 2021). Therefore, this paper applied the same GSEA-based approach to analyze mRNA expression data of tumor and normal CRC tissue derived from human colonic biopsy samples by defining and comparing gene expression signatures (i.e., gene lists ranked by differential expression) (15).…”
Section: Introductionmentioning
confidence: 99%